Obtaining Patient-Reported Outcomes Electronically With “OncoFunction” in Head and Neck Cancer Patients During Aftercare - Zebralla, Veit; Müller, Juliane; Wald, Theresa; Boehm, Andreas; Wichmann, Gunnar; Berger, Thomas; Birnbaum, Klemens; Heuermann, Katharina; Oeltze-Jafra, Steffen; Neumuth, Thomas; Singer, Susanne; Büttner, Matthias; et al. (Frontiers in Oncology, 2020)
The disease and treatment of patients with head and neck cancer can lead to multiple late and long-term sequelae. Especially pain, psychosocial problems and voice issues can have a high impact on patients' health-related quality of life. The aim was to show the feasibility of implementing an electronical PROM in patients with head and neck cancer (HNC).The program "OncoFuntion" has been implemented and continuously refined, driven by the practice in our department to assess Patient Reported Outcomes (PRO) based on the International Classification of Functioning in tumor aftercare. The new version of "OncoFuntion" was evaluated by 20 head and neck surgeons and radiation oncologists in an interview.From 7/2013 until 7/2017, 846 patients completed the PROM during 2833 of 3610 total visits (78.5%). The development of the latest software version and the implemented add -ins lead to high rates of approval in the evaluation. The number of errors and the needed time for the tasks also decreased (6 vs. 0 errors, 1.35 vs 0.95 minutes; p<0.01). There is a high approval rate for the use of PRO in clinical routine.Using a PROM leads to improved data acquisition in daily HNC patients' follow-up. An accessory timeline allowed for seeing results of former consultations and their visualization simplified structured examinations. This provides an easy-to-use representation of the patient's functional outcome to help find the most appropriate aftercare, considering all aspects of the patient's life.